Effects of the physiological state of five yeast species on H(+)-ATPase-related processes - Kotyk, A; Georghiou, G (Folia microbiologica, 1993)
Effects of starvation and glucose preincubation on membrane potential, ATPase-mediated acidification and glutamic acid transport were studied in yeast species Saccharomyces cerevisiae, Schizosaccharomyces pombe, Dipodascus magnusii, Lodderomyces elongisporus and Rhodotorula gracilis. The membrane potential was highest after preincubation with glucose in all species but L. elongisporus and R. gracilis. In all cases the membranes were depolarized in the presence of 20 mmol/L KCl and hyperpolarized with 50 mumol/L diethylstilbestrol (DES). The extracellular acidification caused by addition of glucose was highest after preincubation with glucose in all cases except in R. gracilis where there was none. In all cases except in R. gracilis addition of KCl caused a marked increase in the acidification rate. Addition of DES with glucose caused a large decrease in rate in S. cerevisiae but had much less effect on the other species. Transport of glutamic acid was clearly increased after pretreatment with glucose in S. cerevisiae, S. pombe and D. magnusii (mainly due to enhanced synthesis of the carrier) but actually decreased in R. gracilis and L. elongisporus. Addition of DES had an inhibitory effect in all species but much more pronounced in S. cerevisiae and S. pombe than in others. In general, both the acidification and the transport of glutamate were enhanced after preincubation with glucose but much more so in the semianaerobic species, such as S. cerevisiae, than in the strict aerobes (R. gracilis) where the effect was occasionally negative. There was no relationship between the ATPase-mediated acidification and the membrane potential.
Keywords: kinetika; Saccharomyces cerevisiae; membránové potenciály; diethylstilbestrol; glukosa; kvasinky; Biological Transport, Active; koncentrace vodíkových iontů; glutamáty; Glutamates; Membrane Potentials; Proton-Translocating ATPases; Yeasts; Rhodotorula; Hydrogen-Ion Concentration; Schizosaccharomyces; Diethylstilbestrol; protonové ATPasy; Kinetics; Species Specificity; Glutamic Acid; kyselina glutamová; druhová specificita; aktivní transport; Saccharomycetales; Glucose